16p13.11 Microdeletion in a Patient With Hemiconvulsion-Hemiplegia-Epilepsy Syndrome: A Case Report. (January 2015) - Miteff, Christina I.; Smith, Robert L.; Bain, Nicole L.; Subramanian, Gopinath; Brown, Janis E.; Kamien, Ben
We describe a patient with hemiconvulsion-hemiplegia-epilepsy syndrome. The pathophysiology of hemiconvulsion-hemiplegia-epilepsy syndrome remains uncertain and there are probably multiple potential contributing factors. Our patient had a chromosomal 16p13.11 microdeletion that confers susceptibility to various types of epilepsy. This is the first report detailing an association of hemiconvulsion-hemiplegia-epilepsy syndrome with a 16p13.11 deletion and identifies another potential causal factor for hemiconvulsion-hemiplegia-epilepsy syndrome.